Phytochemical Evaluation and Antinociceptive Effect of the Extract of Ferula persica Willd. Oleo-gum-resin - Mahsa Sabernavaei; Marjan Shariatpanahi; Samin Dokht Hashemi; Paria Sharafi-Badr; Asie Shojaii (Traditional and Integrative Medicine)
Ferula persica Willd. is a native plant of Iran known for its anti-spasmodic, analgesic, and anti-inflammatory properties in Persian medicine. This study investigated the antinociceptive effects of the oleo-gum-resin extract of F. persica in mice, as well as its chemical composition. The hydroalcoholic extract of F. persica oleo-gum-resin was prepared using the maceration method. Mice were randomly divided into six groups: a normal saline group (negative control), a dimethyl sulfoxide group, three groups receiving different doses of the hydroalcoholic extract (50 mg/kg, 100 mg/kg, and 200 mg/kg), and a sixth group (positive control) receiving Ketoprofen. To assess the analgesic effects of the extract, four tests were conducted: writhing, hot plate, tail flick, and formalin tests. Additionally, the chemical compounds, total phenolic content, and total flavonoid content of the oleo-gum-resin extract were determined. The findings demonstrated that the extract at doses of 50, 100, and 200 mg/kg effectively reduced pain and the analgesic effect was dose dependent. A significant difference was observed between the control and treatment groups across all four tests. The 200 mg/kg dose exhibited the greatest analgesic effect in both the acute and chronic phases of the formalin tests. Some chemical compounds of the gum such as flavonoids may be responsible for its analgesic effect. According to this study, F. persica gum extract can alleviate pain caused by thermal and chemical stimuli. These findings support the traditional use of F. persica gum in managing painful conditions. Further studies are needed to investigate effectiveness  of F. persica oleo-gum-resin in pain management and the possible mechanisms of its analgesic effects.